Bank as a venture capitalist - Kumar Rishabh (University of Basel, Center of Business and Economics (WWZ), 2021)
Banks all over the world show interest in acting as venture capitalists. In this paper, I argue that banks offer venture capital (VC) financing along with traditional (collateralized) loans in response to the natural constraints of the hidden information that they face. Innovative entrepreneurs pursue new technology that promises high return but runs a high risk of failure. The more innovative entrepreneurs also have higher reservation utility. This interaction between type-dependent returns and reservation utility creates a situation where collateral alone is not sufficient to screen entrepreneurs, and the uninformed bank needs an additional screening device. VC fulfils that role.
Keywords: G21; G24; D86; 330; Bank; Venture Capital; Collateral; Debt; Screening